Study on Problem of Knowledge in William Wordsworth Poetry: Exploring the Interplay of Knowledge and Imagination in William Wordsworth's Poetry (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Knowledge establishes the awareness of the outside world and the awareness of one's own self. The marvelous world around the individual and the inner self of the individual are the wellsprings of knowledge. Sense insight, inference and memory are the regularly acknowledged method for knowledge. The object of art mirrors the inner soul of the item imitated which is appeared by the artist's imagination. Wordsworth places imagination as the personnel that empowers the psyche to conceptualize the presence of boundlessness in the limited world. The awareness of the perceptual world is supplanted by the theoretical presence of endlessness. The character with the stream and the street as individual voyagers is the sensation of fellowship with the objects of nature. The differentiating remarkable articles are acknowledged as the workings in total agreement. A work of art is basically the inside made outer, coming about because of a creative process working under the motivation of feeling, and exemplifying the joined result of the writer's discernments, thoughts, and feelings. The essential source and subject matter of a sonnet, subsequently, are the attributes and activities of the writer's own psyche or on the other hand in the event that parts of the outside world, these just as they are changed over from reality to poetry by the feelings and tasks of the artist's brain